Pengaruh Sosial Media Tiktok Dalam Pembangunan Karakter Pancasila - Daffa Fadhlurrohman; Fahmi Ibrahim; M. Rizky Irdiyansyah; Peni Apriyanti; Rasya Aditya Hilman; Supriyono Supriyono (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to identify and analyze the influence of TikTok social media on Pancasila character building of the younger generation, including its positive and negative impacts. The research method used was a quantitative survey through an online questionnaire using Google Forms. The research population was TikTok users, with a sample of 17 purposively selected respondents. The results showed that TikTok has various influences on the character of the younger generation. Positively, TikTok is considered to be able to increase creativity, the spirit of nationalism, tolerance, and work ethic. However, negative impacts were also found, such as confusion in understanding national values, decreased mutual respect, and productive motivation. The most vulnerable areas to be affected are the moral, ethical, and national spirit aspects. The conclusion of this study is that TikTok has the potential to support Pancasila character building if used appropriately, but also presents risks that need to be managed through media literacy, content monitoring, and character education. Collaborative efforts between government, educators, and users are needed to maximize the positive impact of this platform.